Collective reflection in practice: an ethnographic study of Swedish police training. Issue 6 (1st November 2016) - Rantatalo, Oscar; Karp, Staffan
Abstract: Although reflection has been viewed as an individual process, increased attention has been given to how reflective processes are socially anchored. The present article contributes to this knowledge through an examination of how collective reflection is enacted in the context of police education. The article is based on a one-year ethnographic study of police recruits undergoing training, and the main sources of data collection were participant observations and field interviews. The data were inductively analysed, and a model that differentiates amongst 'specular', 'dialogic' and 'polyphonic' reflection processes is presented. The findings suggest that collective reflection involving multiple individuals adds complexity to reflective processes and that these processes may take on more diverse forms than has been acknowledged, as previous research has mainly focused on dialogic collective reflection. The implications of these findings, such as how increased complexity may counteract the benefits of collective reflection, are also discussed.